PENINGKATAN KEMAMPUAN ANALISIS MAHASISWA MELALUI PENDEKATAN CONTEXTUAL TEACHING LEARNING (CTL) DALAM PEMBELAJARAN PENGANTAR KEPENDUDUKAN - Nurdiyana, Tutung (Jurnal Vidya Karya, 2012)
This paper is the result of the Classroom Action Research based on the problems faced in the Population Introduction class of Sociology Education Program FKIP UNLAM. It is studied in this paper wether the Contekstual Teaching Learning (CTL) approach can improve the analytical skills of students in the classroom? Can students master the material properly after following Contextual Teaching Learning (CTL) approach? How do student perceptions and impression about the Contextual Teaching Learning (CTL) approach? The method of the study is class action research. It uses qualitative methods approach. The research carried out in 2 cycles consists of four stages of action research, namely: the action planning phase, implementation phase of the action, the stage of observation, and reflection phases. The study finds that CTL approach can improve the students analytical skills and receive positive response from the students.